Impact of treatment with rosuvastatin and atorvastatin on cardiovascular outcomes: evidence from the Archimedes-simulated clinical trials - Colivicchi F; Sternhufvud C; Gandhi SK (Dove Medical Press, 2015)
Furio Colivicchi,1 Catarina Sternhufvud,2 Sanjay K Gandhi3 1Cardiology Division, Emergency Department, San Filippo Neri Hospital, ASL Roma E, Rome, Italy; 2Global Payer Evidence and Pricing, AstraZeneca R&D, Mölndal, Sweden; 3Global Health Economics and Outcomes Research, TEVA Pharmaceuticals, Frazer, PA, United States Objective: No clinical trials have been conducted to directly compare the effect of the two high-intensity statins, rosuvastatin and atorvastatin, on cardiovascular outcomes. However, three such trials have been computer-simulated using the Archimedes model, an individual-based simulation of human physiology and behaviors, treatment interventions, and health care systems. The results are reviewed here.Methods: The first simulated trial assessed clinical outcomes in patients receiving available doses of the two drugs. The second assessed the impact of initial treatment decisions, while the third assessed the effect of switching from rosuvastatin to atorvastatin.Results: In the first simulated trial, treatment with rosuvastatin was estimated to result in greater reductions than treatment with atorvastatin in major adverse cardiac event (MACE) rates at 5 years and 20 years at all doses examined (relative risk [RR]: 0.897, 0.888, and 0.930 at 5 years for rosuvastatin 20 mg vs atorvastatin 40 mg, rosuvastatin 40 mg vs atorvastatin 80 mg, and rosuvastatin 20 mg vs atorvastatin 80 mg, respectively; all P<0.05). In the second simulated trial, outcomes were significantly better in patients initially prescribed rosuvastatin than in those initially prescribed atorvastatin (RR of MACE at 5 years: 0.918; P<0.001). In the third simulated trial, risk of MACE was significantly greater in patients switching from rosuvastatin to atorvastatin than in those remaining on rosuvastatin (RR at 5 years: 1.109; P<0.001).Conclusion: The results of these simulated clinical trials suggest improved outcomes among patients receiving rosuvastatin relative to patients receiving atorvastatin in various clinical settings.Keywords: statins, rosuvastatin, atorvastatin, simulated clinical trials, outcome assessment